Pregnancy and Labor Epidural Effects on Gastric Emptying: A Prospective Comparative Study. (1st February 2022) - Bouvet, Lionel; Schulz, Thomas; Piana, Federica; Desgranges, François-Pierrick; Chassard, Dominique
Abstract : Background: The lack of reliable data on gastric emptying of solid food during labor has led to some discrepancies between current guidelines regarding fasting for solid food in the parturient. This prospective comparative study aimed to test the hypothesis that the gastric emptying fraction of a light meal would be reduced in parturients receiving epidural analgesia and with no labor analgesia compared with nonpregnant and pregnant women. Methods: Ten subjects were enrolled and tested in each group: nonpregnant women, term pregnant women, parturients with no labor analgesia, and parturients with epidural labor analgesia. After a first ultrasound examination was performed to ensure an empty stomach, each subject ingested a light meal (125 g yogurt; 120 kcal) within 5 min. Then ultrasound measurements of the antral area were performed at 15, 60, 90, and 120 min. The fraction of gastric emptying at 90 min was calculated as [(antral area 90 min / antral area 15 min ) – 1] × 100, and half-time to gastric emptying was also determined. For the Parturient–Epidural group, the test meal was ingested within the first hour after the induction of epidural analgesia. Results: The median (interquartile range) fraction of gastric emptying at 90 min was 52% (46 to 61), 45% (31 to 56), 7% (5 to 10), and 31% (17 to 39) for nonpregnant women, pregnant women, parturients without labor analgesia, and parturients with labor epidural analgesia, respectively ( P < 0.0001). The fraction of gastric emptying at 90 min was statistically significant and lower in the Parturient–Epidural group than in the Nonpregnant and Pregnant Control groups. In addition, the fraction of gastric emptying at 90 min was statistically significant and lower in the Parturient–No-Epidural group than in the Parturient–Epidural group. Conclusions: Gastric emptying in parturients after a light meal was delayed, and labor epidural analgesia seems not to worsen but facilitates gastric emptying. This should be taken into consideration when allowing women in labor to consume a light meal. Abstract : Gastric emptying after a light meal was delayed in parturients compared with nonpregnant women and term pregnant women not in labor. However, epidural analgesia commonly used in labor seems not to worsen gastric emptying in parturients, but rather facilitates it.